Sequential paternal haploidentical donor liver and HSCT in EPP allow discontinuation of immunosuppression post‐organ transplant. (2nd June 2021) - Malkiel, Sarah; Sayed, Blayne A.; Ng, Vicky; Wall, Donna A.; Rozmus, Jacob; Schreiber, Richard A.; Faytrouni, Farah; Siddiqui, Iram; Chiang, Kuang‐Yueh; Avitzur, Yaron
Abstract: Background: EPP is characterized by photosensitivity and by liver disease. When LT is performed in EPP, recurrence often occurs in the allograft due to ongoing protoporphyrin production in bone marrow. Therefore, curative treatment requires allogeneic HSCT after LT. Long‐term immunosuppression could be spared by using the same donor for both transplants. Methods: A 2‐year‐old girl with EPP in liver failure underwent liver transplant from her father. Transfusion and apheresis therapy were used to lower protoporphyrin levels before and after liver transplant. Ten weeks after liver transplant, she underwent HSCT, using the same donor. Conditioning was with treosulfan, fludarabine, cyclophosphamide, and ATG. GVHD prophylaxis was with abatacept, methotrexate, MMF, and tacrolimus. We followed the patient's erythrocyte protoporphyrin and liver and skin health for 2 years after transplant. Results: After hematopoietic stem cell engraftment, a decline in protoporphyrin levels was observed, with clinical resolution of photosensitivity. Liver biopsies showed no evidence of EPP. Mild ACR occurred and responded to steroid pulse. Two years post‐HSCT, the patient has been weaned off all immunosuppression and remains GVHD and liver rejection free. Conclusions: Sequential liver and HSCT from the same haploidentical donor are feasible in EPP. This strategy can allow for discontinuation of immune suppression.